The state of «the pituitary gland - thyroid gland system» in the young men with undifferentiated dysplasia of the connective tissue - P. A. Yurchenko; L. A. Levina (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова, 2013)
To investigate the state of «the pituitary gland-thyroid gland system» in the patients with undifferentiated dysplasia of the connective tissue (UDCT) 83 young men of the call up age (18.2±0.4 y.o.) were examined. The control group consisted of 26 practically healthy young men of the same age (18.5±0.2 y.o.). Autoimmune thyroiditis (AIT) was diagnosed in 32.5 % of the men with UDCT. The rate of the internal (visceral) phenotypical signs of UDCT in this group was significantly higher than in the men with UDCT but without thyroid problems.